Pengembangan Media Convertible Book Berbasis Scientific Approach Untuk Meningkatkan Pemahaman Konsep dan Karakter Peduli Lingkungan - Ariani Rahmawati; Anwar Senen (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2021)
The aims of the research are (1) to develop a convertible book bases on scientific approach to improve the concept understanding and care-for-environmental character, (2) to reveal the effectiveness of the developed convertible book to improve the concept understanding and care-for-environmental character of grade IV students of elementary schools in Moga sub-district. The research uses Research and Development (R & D) model with reference to product development by Borg & Gall. The subject of research are students of elementary schools in Moga sub-district. The validity of the developed convertible book was analyzed by converting to five quantitative criteria. The effectiveness of the convertible book in improving the concept understanding and care-for environmental character was analyzed by N-gain score, t-test and MONOVA at the significance level of 0.05. The result of the research showed that the convertible book fulfilled the feasibility criteria according to the validation by material expert and media expert, teachers’ responses and students’ responses which was in a good of very feasible category. The convertible book was effective to improve the students’ concept understanding and care-for-environmental character. The result of the t-test at sig. 0.05 showed the effect of the use of the media and test MANOVA, that there was significant effect between experiment and control class at 0.00.